LEMBAGA KEUANGAN MIKRO BINAAN LSM UNTUK PENGENTASAN KEMISKINAN STUDI LKM LEMBAGA KEUANGAN PEREMPUAN LP2M DI SUMTERA BARAT - Ariesta Ariesta (Universitas Islam Negeri Imam Bonjol Padang, 2013)
The research describes about the accessibility and the sustainability of Micro Financial Organization whichnamed by LP2M as Lembaga Keuangan Perempuan (LKP) on the decreasing of poverty. In general, the purposesof research are to describe the accessibility and the sustainability of LKP LP2M on the guided poor citizenLP2M and to explain the causes of existence of Micro Financial Organization in decreasing the poverty. Themethod used in this research was descriptive qualitative. The data were gotten by deep interview, observation,and document. The research result has shown that LKP LP2M gave accessibility towards guided poor citizenLP2M because LKP was easy to be reached by the group members and the source of financial capital was easyto get. The practice of LKP in giving access on KPUK and group members is one of the forms of social dualitypractice. It is a kind of mirror of mutual process between actors who made the LKP rules and social groupwhich grouped in KPUK.